Meningkatkan Sikap Semangat Kebangsaan Siswa Melalui Model Value Clarification Technique (VCT) Di Kelas Tinggi Sekolah Dasar - Fina Alfiana; Dyah Lyesmaya; Din Azwar Uswatun (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research aims to describe an increase in the attitude of the national spirit of students through using the Value Clarification Technique (VCT) model in high school elementary school. The method used is class action research design model chemistry & Mc. Taggart. Participants in this reaseach were 17 students of fifth grade in SD Aisyiyah, Sukabumi City, 2018-2019 academic year. Instruments for collecting data used in this study consisted of interviews, observation sheets, questionnaires, attitude scale (likert), field notes and documentation consisting of 2 cycles. The results of the pre-cycle research on the attitude of the national spirit of students gained 39% classical completeness in the weak category. In the first cycle, the attitude of the national spirit showed 62% classical completeness with a strong category. In the second cycle, the attitude of the national spirit showed 82% classical completeness with a very strong category. Based on the results obtained it can be concluded that through the VCT model it can improve the attitude of students' national spirit.